Implementation of the Traffic Light System in Norwegian salmon aquaculture - success or failure for whom? - Michaelsen-Svendsen, Bjørnar (UiT The Arctic University of Norway, 2019)
Since Norwegian Atlantic salmon aquaculture developed into a viable industry in the 1960s, it has grown into one of Norway’s most important sectors. A crucial factor influencing this growth has been the development of a management system which has facilitated the growth in an advantageous way. In the latter part of 2017, a new aquaculture management system started, called the Traffic Light System. This system came as a result of a six years long period of public and political discourses. The Traffic Light System represented a significant shift in how the industry is managed and how the continued growth in production will happen. The aim of this thesis was to investigate if the implementation process leading up to the initiation of the Traffic Light System was a success or failure, from the perspective of the government and different interest groups. The period analysed was from the Gullestad Committee in 2011 to the initiation of the Traffic Light System. To answer the aim of this thesis, the integrated framework for implementation studies developed by Søren C. Winters was applied. The result showed that when applying Winters framework, the success or failure of a policy depends on the perspective used when analysing it. From the Norwegian government’s point of view the process has been a success, while from the perspective of the interest groups it has been neither a success nor a failure.